Exploring newly qualified nurses' experiences of support and perceptions of peer support online: A qualitative study. Issue 19 (19th April 2021) - Jenkins, Catharine; Oyebode, Jan; Bicknell, Sarah; Webster, Natalie; Bentham, Peter; Smythe, Analisa
Abstract: Aims and Objectives: To explore newly qualified nurses' support needs and their perceptions of online peer support. Background: The experience of being a newly qualified nurse is stressful and isolating. Support from colleagues and peers can enhance perceptions of competence and confidence in newly qualified nurses, improve well‐being and aid retention. However, despite initiatives such as preceptorship, support needs may remain unmet in busy clinical environments. Online support has potential to offer a partial solution to professional isolation, but there is a lack of research into how technology can support nurses' emotional and social well‐being. Design: A qualitative exploratory study was designed, employing semi‐structured focus groups, analysed using thematic analysis. The study is reported in accordance with the COnsolidated criteria for REporting Qualitative research checklist. Methods: Eight focus groups, supplemented by one individual interview, were conducted with newly qualified nurses between June 2018–January 2019. Findings: Two main themes arose. The first was Drowning, a lot of the time with two sub‐themes: (i) Feelings and emotions about being a Newly Qualified Nurse: 'Absolutely terrified' and (ii) Support within the role: 'Somebody you can count on'. The second was Potential advantages and disadvantages of online modality: 'Somebody is going to get in that phone!' which included three sub‐themes (i) Potential advantages, (ii) Potential disadvantages and (iii) Preferences and recommendations. Conclusions: This study demonstrates that if barriers can be overcome, then online support has potential to contribute to newly qualified nurses' well‐being. Further research is needed to explore technical and ethical issues around online support and evaluate its effectiveness for newly qualified nurses. Relevance to clinical practice: Online support has the potential to add to existing strategies to support nurses during stressful times. This may be particularly relevant when many staff are working under increased pressure due to the COVID‐19 pandemic.